In Vitro Endothelial Cell Proliferation Assay Reveals Distinct Levels of Proangiogenic Cytokines Characterizing Sera of Healthy Subjects and of Patients with Heart Failure - Rebecca Voltan; Giorgio Zauli; Paola Rizzo; Alessandro Fucili; Micaela Pannella; Roberto Marci; Veronica Tisato; Roberto Ferrari; Paola Secchiero (Hindawi Limited, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52±7.6 years; n=46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29±8.6 years; n=20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n=11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n=18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P<0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.